2022
DOI: 10.3345/cep.2021.00129
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of breastfeeding and factors associated with its delay among mothers at discharge from a single hospital

Abstract: Background: According to the National Family Health Survey -4, in India, 78.9% of deliveries occur in institutions, although only 42.6% of new mothers initiate breastfeeding within one hour of delivery. Purpose:To estimate the proportion of early initiation of breastfeeding (EIBF) among new mothers at discharge from a tertiary care hospital and identify the determinants of delayed initiation of breastfeeding among them. Methods: This was a hospital-based analytical cross-sectional study of 108 new mothers.Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Despite a wealth of data on various aspects of EIB, 15 , 17 , 20 recent evidence on the relationship between health facility delivery and EIB appears to be limited in the context of SSA. As a result, the current study examined the relationship between health facility delivery and EIB in eleven SSA countries using the most recent DHS datasets spanning 2018–2021, to uncover the sub‐region's evidence on the subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a wealth of data on various aspects of EIB, 15 , 17 , 20 recent evidence on the relationship between health facility delivery and EIB appears to be limited in the context of SSA. As a result, the current study examined the relationship between health facility delivery and EIB in eleven SSA countries using the most recent DHS datasets spanning 2018–2021, to uncover the sub‐region's evidence on the subject.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 This is understandable given the importance of trained healthcare providers in various health facilities in ensuring the health of mothers and newborns. 20 In contrast, some evidence suggest that a significant proportion of children born in health facilities do not receive EIB. 21 , 22 Overall, these series of evidences emphasize that EIB advocacy may be ineffective if separated from healthcare delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various barriers for early initiation have been mentioned in different studies such as maternal lassitude and uncomfortable breastfeeding position due to post-delivery pain, 15 late transfer of mother from delivery room to the observation area, and high delivery load. 16 At our institute, we noticed only 61% of stable babies delivered vaginally received breastfeeding within 1 hour of birth.…”
Section: Introductionmentioning
confidence: 99%
“…As in the current review, Chopel et al concluded that the awareness of benefits was enough to inspire adolescents to initiate breastfeeding. The mother's poor knowledge about breastfeeding was the factor and barrier to the delay of early initiation of breastfeeding baby (Mary et al, 2022). Two more studies reveal that the mother's lack of knowledge about breastfeeding was the factor in to delay of early initiation of breastfeeding (Petruţ et al, 2019, Ahmed et al, 2019.…”
Section: Introductionmentioning
confidence: 99%